Computer Musical Creative Work in the Russian Initial Vocational Education System - Gorbunova, Irina B. (2020)
The development of new music technologies necessitates changes in the content of music education. Musical pedagogy is faced with the task of educating creative musicians who are capable of innovative activities and inventive musical thinking. Therefore, primary music education should introduce creative learning technologies aimed at developing students’ creative abilities. This article analyzes the content of students’ musical and creative activities in the field of music computer technologies (MCT) illustrated by the subject “Computer Music Creative Work.” The theoretical and experimental study led us to conclude that this course not only develops creative abilities but also establishes conditions for the comprehensive and harmonious development of students’ personalities.